2023
DOI: 10.4995/wrs.2023.18268
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal factors affecting the probability of survival between birth and weaning in rabbits

Abstract: The aim of this study was to analyse the relationships between kit birth weight and litter size with kit survival from birth to weaning, and to estimate the effects of place of birth, nest quality, cannibalism, lactation, parity order, season and sex. A total of 1696 kits from 82 females of the ITLEV2006 synthetic line were used in this study. A logistic regression was performed. Kit birth weight was directly related to the probability of the kit’s survival from birth to weaning, and increasing birth weight by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The perinatal weight of kits has been directly linked to preweaning survival; kits with lower birth weights have a lower probability of survival [ 6 , 15 ] due to a reduction in energy reserve and thermoregulatory capacity [ 16 ]. In our study, 26% of born kits perished before weaning, which is consistent with the values reported in maternal rabbit lines [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The perinatal weight of kits has been directly linked to preweaning survival; kits with lower birth weights have a lower probability of survival [ 6 , 15 ] due to a reduction in energy reserve and thermoregulatory capacity [ 16 ]. In our study, 26% of born kits perished before weaning, which is consistent with the values reported in maternal rabbit lines [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection core is located in Baba Ali, Algiers, Algeria, where the genetic resources are managed. As a matter of fact, in Algeria, many studies were carried out to describe the effects of genotype and crossbreeding parameters on feed and feeding, growth and zootechnical performance of the new synthetic breed (Zerrouki et al, 2014;Sid et al, 2018;Belabbas et al, 2021;Belabbas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%